2008
DOI: 10.3354/dao01971
|View full text |Cite
|
Sign up to set email alerts
|

Control of freshwater fish louse Argulus coregoni: a step towards an integrated management strategy

Abstract: Harmful infections by ectoparasites of the genus Argulus occur repeatedly in freshwater fish farming operations where the management has largely been ineffective. Preventative methods and regular monitoring are rarely applied, so that chemical interventions become necessary. According to the Integrated Pest Management (IPM) approach, a sustainable management or control program for a parasite should be based on knowledge of the ecology of the parasite along with adoption of several prevention and control method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 56 publications
0
16
0
2
Order By: Relevance
“…Moreover, the residuals of the synthetic pesticides have been consistently burdening the eco-toxicity (Costello et al 2001) day by day. Indiscriminate use of the insecticides very often leads to rapid development of resistance (Hakalahti-Sirén et al 2008), so control of pests and parasites is currently hindered by the small number of effective products available in the market (Jonsson and Piper 2007). In this context, it is to be mentioned that different plant derivatives can be better alternatives and safer (De Albuquerque et al 2007;Dos Santos et al 2011;Banerjee and Saha 2013) for management of diseases of domesticated animals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the residuals of the synthetic pesticides have been consistently burdening the eco-toxicity (Costello et al 2001) day by day. Indiscriminate use of the insecticides very often leads to rapid development of resistance (Hakalahti-Sirén et al 2008), so control of pests and parasites is currently hindered by the small number of effective products available in the market (Jonsson and Piper 2007). In this context, it is to be mentioned that different plant derivatives can be better alternatives and safer (De Albuquerque et al 2007;Dos Santos et al 2011;Banerjee and Saha 2013) for management of diseases of domesticated animals.…”
Section: Introductionmentioning
confidence: 99%
“…Se llevó a cabo un tratamiento de eliminación de los parásitos por la técnica de remoción mecánica (RM) frotando a los peces con las mallas de captura (Hakalahti-Sirén et al, 2008) y además con agua a presión, tratando de dañar lo menos posible a los organismos. Los peces desparasitados (299) fueron colocados en un estanque de geomembrana de 20 m 3 para su observación.…”
Section: Resultsunclassified
“…Hakalahti -Sirén et al, (2008) evaluaron diferentes tratamientos para eliminar A. coregoni y A. foliaceus de Oncorhynchus mykiss y Salmo trutta, incluyendo la remoción mecánica (RM) y diversos compuestos químicos como permanganto de potasio (0.01 g L -1 ), cloruro de sodio (0.6 ml L -1 ) y una solución de verde malaquita con formol (20 g L -1 ). Sus resultados demuestran que el permanganato de potasio provocó una mortalidad del 100 % del ectoparásito.…”
Section: Resultados Y Discusiónunclassified
“…However, Straus and Griffin (2001) demonstrated that the exposure to 0.9 mg/L potassium permanganate for 4 h resulted in over 95% mortality of Ichthyophthirius multifiliis theronts, and the dose of 1.0 mg/L could prevent the initial infestation of juvenile channel catfish and blue tilapia by this parasite. Hakalahti-Siren et al (2008) also reported that both juvenile and adult fish lice Argulus coregoni were highly sensitive to potassium permanganate treatments, exposure to which for over 30 min resulted in 100% mortality at 10 mg/L. The discrepancy among these results indicated that insecticide activity of potassium permanganate is highly dependent on the concentration and parasite species.…”
Section: Discussionmentioning
confidence: 99%